THE RELATIONSHIP BETWEEN PARENTING STYLE AND PEER SOCIAL SUPPORT WITH ADOLESCENT MENTAL HEALTH AT SMP NEGERI 2 PAKUHAJI - Firda Sunarti Sunarti; Osep Yasier Almunsiri; Lailatul Fadilah (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Background: Adolescence is a transitional period from childhood to adulthood characterized by rapid changes in physical, emotional, social, and psychological aspects, making adolescents vulnerable to mental health disorders. Adolescent mental health is influenced by parenting styles (democratic, authoritarian, permissive) that shape personality, as well as peer support, which is the primary source of emotional support. Research Objective: To determine the relationship between parenting and peer social support with adolescent mental health at SMP Negeri 2 Pakuhaji. Research Methods: This type of research is correlational analytic with a cross-sectional approach. The sampling technique used was proportionate stratified random sampling. The sample used in this study was 102 respondents. The instruments used were parenting questionnaire, Social Provision Scale (SPS) questionnaire and Self Reporting Questionnaire (SRQ-20). Research results: The results of statistical tests showed that the p-value between parenting patterns and adolescent mental health was 0.000 <0.05. The p-value between peer social support and adolescent mental health is 0.000<0.05. Conclusion: There is a significant relationship between parenting and peer social support with adolescent mental health at SMP Negeri 2 Pakuhaji.